Green Human Resource Management Practices and Employee Engagement in Information Technology-Enabled Services Companies - Zafra, Josephine; Guballo, Jayvie (Journal of Management Studies and Development, 2025)
This research explored how employees in Business Process Outsourcing (BPO) companies in Makati City adopted Green Human Resource Management (GHRM) practices to support environmental sustainability and strengthen employee engagement. Despite Makati’s unique dynamics, few studies have examined the link between GHRM initiatives and engagement in the Information Technology-Enabled Services (ITES) sector. This study addressed that gap, offering insights for organizations aiming to enhance sustainability programs while keeping their workforce engaged. As more BPO firms prioritize green initiatives, understanding how GHRM influences employee behavior and motivation becomes essential. The research focused on green recruitment, environmental training, and sustainability-based performance evaluations, finding a positive relationship between GHRM strategies and employee engagement. When companies adopt environmentally responsible policies, employees respond with increased loyalty and participation. The study also highlighted the role of renewable energy sources—solar panels, wind turbines, and geothermal systems—as alternatives to traditional electricity. Promoting these technologies helps reduce carbon emissions and reliance on the power grid. Overall, the findings deepen the understanding of how green HR practices can drive both organizational and environmental benefits. BPO firms, especially in the ITES sector, are encouraged to implement GHRM strategies not only for ecological reasons but also to foster a more engaged and purpose-driven workforce.